High Temperature Deformation Characteristics of an Alumina‐Forming Stainless Steel. Issue 7 (18th March 2019) - Luo, Rui; Yang, Yutong; Bian, Huakang; Chen, Leli; Ouyang, Lingxiao; Peng, Ching‐Tun; Gao, Pei; Xu, Guifang; Cheng, Xiaonong
Abstract : This investigation study deformation characteristics of an innovative stainless steel, alumina‐forming austenitic (AFA) Fe–20Cr–30Ni–0.6Nb–2Al–Mo steel, at elevated temperature, and those isothermal hot compression tests are performed with various temperatures and strain rates. The results show that as the temperature decreases (or as strain rate rised), the stress level increases. On the other hand, in order to better predict the flow stress behavior, a modified constitutive relationship model is established based on the strain‐compensated Arrhenius‐type equation, and the accuracy of this modified model is examined statistically. Furthermore, by comparing with the experimental results, this modified constitutive model is proved to be able to precisely predict the high temperature flow behaviors of the AFA alloy. In addition, processing maps of this alloy are also constructed, and expanded instability regions are found with higher strain rate values (above 0.18 s −1 ). Moreover, from the microstructure characterization, the features of both adiabatic shear bands and flow localization are formed in those samples of instability regions. Eventually, the optimum high temperature deformation parameters can be determined as 1050–1120 0.01–0.1 s −1 and 1120–1150 °C/10 −0.5 –10 −1.5  s −1 for this AFA alloy. Abstract : This paper focuses on hot deformation behavior of an alumina‐forming stainless steel. A modified constitutive model of this alloy is established based on the strain‐compensated equation. In addition, processing maps of this alloy are also constructed. Form the microstructure characterization, the features of both adiabatic shear bands and flow localization are formed in this alloy of instability regions.